The art and science of community relations: Procedural fairness at Newmont's Waihi Gold operations, New Zealand. (June 2017) - Lacey, Justine; Carr-Cornish, Simone; Zhang, Airong; Eglinton, Kelvyn; Moffat, Kieren
Abstract: Community relations are an integral part of successful and socially acceptable mining operations. Effective interactions between a mining company and a host community tend to foster mutual understanding and trust, leading to higher levels of acceptance of those operations. The Waihi gold mining operations in New Zealand, which consist of an open pit, several underground operations, a processing facility and waste storage facilities, are well known for their close proximity to their host community. In 2011, the company Newmont Waihi Gold announced a potentially controversial extension to their existing underground operations, which for the first time proposed to extend directly beneath homes in residential Waihi. At the time of this announcement, the company had made no consent application nor held permission to extend their operations. The announcement was the first stage in an extensive three year consultation period with the community to negotiate whether and how the extension might proceed. This paper provides a case study of community relations practice that draws on both quantitative and qualitative research methods to examine the drivers of community acceptance of this extension. This includes results of a survey of community members undertaken prior to the announcement of the proposed extension, which identifies why community members regarded the company as a positive member of their community, and how this contributed to their acceptance of the company. These findings are supported by a series of interviews with key stakeholders from both company and community that interrogate the community relations process and how the mine's extension was negotiated after the initial proposal was announced. Based on these findings, a number of initiatives that were jointly developed by the company, community and other stakeholders through a voluntary, facilitated negotiation process within the legal consenting regime are identified. It is also observed that these negotiations ultimately allowed this complex operation to proceed. Our findings highlight how community relations function in practice, how trust in the relationship between company and community is underpinned by procedural fairness in those interactions, and provide examples of how fair processes are negotiated in context. Highlights: Community relations are critical to socially acceptable mining operations. This paper presents a case study of the Newmont Waihi Gold operations in New Zealand. The case study uses mixed methods to demonstrate the drivers of community acceptance. Procedural fairness is found to be a key factor for successful community relations. The findings highlight examples of how fair processes are negotiated in context.